Avaliação da Concordância intra e interobservador e da acurácia da biópsia de glândulas salivares menores para a classificação da doença de Sjögren - Clarice Garcia Valadares Xavier (2024)
Introduction: Sjögren's disease is characterized by lymphocytic invasion and hypofunction of exocrine glands, mainly the salivary and lacrimal glands. Minor salivary gland biopsy (MSGB) is relevant for its diagnosis, stratification and prognosis. Despite this, previous studies have observed a low concordance in the evaluation of the MSGB, which is due to the use of different histological criteria in its analysis and underestimation of useful histopathological characteristics such as focus scores (FS) and the presence of structures similar to germinal centers (GC). The present study aimed to evaluate the accuracy of MSGB for the diagnosis of Sjögren's Disease and the interobserver and intraobserver reproducibility of histological analysis of MSGBs performed from November 2017 to April 2022 in a university hospital. Methodology: This is a cross-sectional study carried out in two distinct stages. Firstly, medical records and pathology reports of patients who underwent MSGB from November 2017 to April 2022 were reviewed. Sensitivity, specificity, positive, negative predictive values and accuracy were calculated to evaluate the performance of MSGB for patients classified as having Sjögren's disease. To assess interobserver reproducibility, the MSGB reports were reexamined by two pathologists. For intraobserver analysis, all MSGB were independently reviewed twice, at least two months apart, by the same expertise as the pathologist, using a blinded procedure. The standardization proposed by EULAR in 2017 was followed. Results: Inter and intraobserver analyses showed good agreement (Kappa coefficients > 0.6) for dichotomized FS (presence or absence of FS ≥ 1) and and histological diagnosis of focal lymphocytic sialadenitis. Conversely, assessment of structural damage indicated only modest to fair agreement (k ≤ 0.4) for interobserver reliability. Intraclass Correlation Coefficient showed good agreement (ICC >0.6) in both inter and intraobserver analyses. MSGB obtained sensitivity of 86.76%, specificity of 95.42%, positive predictive value of 90.77%, negative predictive value of 93.28% and accuracy of 92.46%. The result was false in 7.54% of cases. Conclusion: In this cross-sectional study, interobserver and intraobserver reproducibility exhibited favorable levels for histological diagnosis of focal lymphocytic sialadenitis, while comparatively lower reliability was observed for the estimation of structural damage. This discrepancy may be the result of pathologists' lesser preparation for damage assessment, compared to the assessment of inflammatory changes. BGSM is a procedure with high sensitivity, specificity, and positive and negative predictive values for diagnosing Sjögren's disease. Imperative enhancement of MSGB reproducibility requires the establishment of robust standardization of histopathological assessment and comprehensive training of pathologists.